Tectonic implications of paleontologic dating of Cretaceous-Danian sections of Eastern Cuba - M. A. ITURRALDE-VINENT; C. DÍAZ-OTERO; A. RODRÍGUEZ VEGA; R. DÍAZ-MARTÍNEZ (Geologica Acta, 2006)
The sedimentary rocks intercalated in volcanic and metavolcanic sections of Mayarí-Baracoa and Sierra del Purial Mountains (Eastern Cuba), yielded Cretaceous through Danian microfossils. In the Mayarí Mountains the Téneme Fm consists of basalts and hyaloclastites with minor intercalations of well-bedded foliated limestone and shaly limestone that in the type area contain a Turonian or early Coniacian planktonic foraminifera assemblage. In the Morel area (Moa-Baracoa massif), back-arc pillow basalts with ribbon cherts include a late Turonian or Coniacian limestone bed intercalated with interbedded organic-rich calcareous shales near the top. The upper part of the Coniacian (?)-Campanian Santo Domingo Fm crops out west of Moa and it consists of finegrained well-bedded volcaniclastic rocks with two intercalated lenses of coarse-grained impure biocalcirudites to biocalcarenites. These rocks yielded a mixed penecontemporaneous planktonic and benthonic microfossil assemblage attributed to the lower part of the late Campanian (Globotruncanita calcarata Zone). At Sierra del Purial, crystalline limestones embedded within the metavulcano-sedimentary Río Baracoa section (Purial metamorphic complex) yielded Campanian microfossils. The Maastrichtian Yaguaneque (=Cañas) limestones crop out extensively in both Mayarí-Baracoa and Purial Mountains. All the formations previously mentioned unconformably overlie and tectonically intermingle with the late Maastrichtian-early Danian clastic rocks of the Mícara and La Picota Fms. Our new dates demonstrate that in the Greater Antilles the PIA (Primitive Island Arc-tholeiite) recorded by the Téneme Fm would be Late Cretaceous in age in opposition to the Lower Cretaceous age proposed for the PIA basalts. The protolith of the Purial metamorphic complex is probably Maastrichtian-early Danian, but certainly Campanian and older in age. This fact suggests that the metamorphism that affected the Purial rocks took place probably in the late Maastrichtian and was coeval with the detachment, exhumation and emplacement of mafic-ultramafic thrust-sheet bodies. This event recorded in Eastern Cuba/Western Hispaniola and Guatemala might have been related to the insertion of thick oceanic ridges into the subduction zone.